Identification of lactic acid bacteria from fermented tea leaves (miang) in Thailand and proposals of Lactobacillus thailandensis sp. nov., Lactobacillus camelliae sp. nov., and pediococcus siamensis sp. nov - Tanasupawat, Somboon; Pakdeeto, Amnat; Thawai, Chitti; Yukphan, Pattaraporn; Okada, Sanae (My University, 2007)
Eighteen rod-shaped homofermentatives, six heterofermentatives, and a coccal homofermentative lactic acid bacteria were isolated from fermented tea leaves (miang) produced in the northern part of Thailand. The isolates were placed in a monophyletic cluster consisting of Lactobacillus and Pediococcus species. They were divided into seven groups by phenotypic and chemotaxonomic characteristics, DNA-DNA similarity, and 16S rRNA gene sequences. Groups I to VI belonged to Lactobacillus and Group VII to Pediococcus. All of the strains tested produced DL-lactic acid but those in Group IV produced L-lactic acid. The strains tested in Groups I, II and V had meso-diaminopimelic acid in the cell wall. Six strains in Group I were identified as Lactobacillus pantheris; five strains in Group II as Lactobacillus pentosus; and four strains in Group V as Lactobacillus suebicus. Two strains in Group VI showed high DNA-DNA similarity for each other and MCH4-2 was closest to Lactobacillus fermentum CECT 562T with 99.5% of 16S rRNA gene sequence similarity. Five strains in Group III are proposed as Lactobacillus thailandensis sp. nov., and MCH5-2T (BCC 21235T=JCM 13996T=NRIC 0671T=PCU 272T) is the type strain which has 49 mol% G+C of DNA. Two strains in Group IV are proposed as Lactobacillus camelliae sp. nov., and the type strain is MCH3-1T (BCC 21233T=JCM 13995T=NRIC 0672T=PCU 273T) which has 51.9 mol% G+C of DNA. One strain in Group VII is proposed as Pediococcus siamensis sp. nov., and MCH3-2T (BCC 21234T=JCM 13997T=NRIC 0675T=PCU 274T) is the type strain which has 42 mol% G+C of DNA.
Keywords: Fermented tea leaves; Lactic acid bacteria; Lactobacillus camelliae; Lactobacillus thailandensis; Pediococcus siamensis